Students' Activeness in Mathematics Learning via Zoom on Algebra Learning Material - Daniatun, Rahma; Qohar, Abd.; Susanto, Hery (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
This research aimed to reveal the students’ activeness in mathematics learning on algebra using Zoom. This research is included in the qualitative research category with a descriptive approach. The collected data were analyzed using descriptive methods by showing the total score, percentage, or average score of each respondent's answer. The results showed that students were very active and motivated in achieving learning goals during learning via Zoom. This research implies that virtual learning is feasible to be encouraged.